A Survey on Data Security and Challenges - Bhattacharya, J; Mistri, J; Biswas, R; Dalui, D; D. Singh,; Rakshit, P; S. Bhattacharyya, (International Journal of Computer Sciences and Engineering, 2020)
Big Data has gained attention and become a hot topic in scientific and industrial fields. Big data refers to large amount of data which is difficult to store and process by using traditional data processing application. The digitization of our day to day activities generated petabyte and exabyte of data. The data coming from heterogeneous sources and maximum data is residing in unstructured way. So, Dealing with this enormous data many challenges occur and security issue is one of them. Some other big data challenges are – dealing with huge volume of data, integrating heterogeneous data source, validating data etc. In this paper, we review different challenges and security issues in big data environments.